Online Learning: Optimism and Psychological Well-Being among Nursing Students - Ananda Fairuz Melawardani; Yusshy Kurnia Herliani; Che An Ahmad; Nur Oktavia Hidayati (Lembaga Publikasi Ilmiah Nusantara, 2026)
The shift to online learning in nursing education presents both opportunities and challenges, particularly concerning student psychological well-being. Optimism plays a crucial role in coping with academic stress, enhancing resilience, and increasing academic satisfaction. Factors such as social support, coping strategies, and time management also influence student psychological well-being. This study aimed to determine the relationship between optimism and the psychological well-being of nursing students in online learning. This study utilized a quantitative correlational design. Stratified random sampling was used to select a sample of 400 students. The study adapted the Psychological Well-being Scale (PWBS) and the Life Orientation Test-Revised (LOT-R) as instruments. Univariate analysis involved frequency and percentage distributions, while bivariate analysis used the Chi-Square test. Results: The study's findings showed a significant value (p<0.001). Among the variables, most students from the Faculty of Nursing at Universitas Padjadjaran exhibited low optimism (53.0%) and low psychological well-being (51.0%). There is a significant relationship between optimism and psychological well-being among nursing students during online learning (p<0.001). These findings highlight the need to evaluate the online learning process and engage with students to identify the reasons behind their low levels of optimism and psychological well-being.